Transradial approach for coronary angiography and intervention in the elderly: A meta-analysis of 777, 841 patients. (1st February 2017) - Alnasser, Sami M.; Bagai, Akshay; Jolly, Sanjit S.; Cantor, Warren J.; Dehghani, Payam; Rao, Sunil V.; Cheema, Asim N.
Abstract: Background: Studies showing an advantage of transradial approach (TR) for coronary angiography and intervention (PCI) compared to the transfemoral approach (TF) predominantly included a younger population. Therefore, we conducted a meta-analysis of published studies to determine the efficacy of TR in the elderly population. Methods and results: A comprehensive search identified 16 studies [3 randomized controlled studies, 13 observational] comprising 777, 841 elderly patients undergoing PCI. TR was used in 99, 201 patients and TF in 678, 640 patients. The results from observational studies showed that TR was associated with a lower rate of vascular complications (0.4% vs. 0.8%, OR 0.36, 95% CI 0.30–0.44), stroke (0.3% vs. 0.4%, OR 0.81, 95% CI 0.66–1.0) and death (2.0% vs. 2.2%, OR 0.51, 95% CI 0.41–0.63). RCTs confirmed findings from observational studies for both significant reduction in vascular complications (2.7% vs. 7%, OR 0.37, 95% CI 0.23–0.60) and stroke (0.4% vs. 1.4%, OR 0.31, 95% CI 0.10–0.97) but showed no effect on mortality (3.3% vs. 2.8%, OR 1.20, 95% CI 0.69–2.09). However, among patients with ST elevation myocardial infarction (STEMI), TR was associated with a mortality benefit (5% vs. 7%, OR 0.48, 95% CI 0.25–0.90, p  = 0.02). Access site crossover rate was higher for TR compared to the TF approach (11% vs. 3%, p  = 0.0003) but there was no difference in contrast media use, procedure duration, fluoroscopy time and door to balloon time for STEMI. Conclusion: TR for PCI in the elderly is associated with a reduced risk of stroke, lower rate of vascular complications overall and a mortality benefit for patients presenting with STEMI. The access site cross rate for TR is higher compared to TF but remains acceptably low. TR should be the preferred strategy for PCI in the elderly to optimize clinical benefit in this high-risk group.